FORMULATING THEORIES OF DAKWAH STUDIES - Nur Syam (IAIN Tulungagung, 2019)
This paper examines the contribution of sociology to the making of dakwah studies. From epistemological point of view, dakwah studies develops through five elements: factors, systems, interpretative, developmentalism and participatory. These five elements can be developed based on sociological theories. Through a sociological approach, dakwah studies will be able to contribute to general discussion on the sociology of Muslim societies. The article further argues the inclusion of social science is a pattern of knowledge development based on the integration of science, namely the phenomenon of dakwah as an object of study, while utilizing other social science as approaches.